ESTIMATION OF LOADING AND HAULING EQUIPMENT PRODUCTION AT PT. BAGUS JAYA ABADI, SORONG CITY, SOUTHWEST PAPUA PROVINCE: ESTIMASI PRODUKSI ALAT MUAT DAN ALAT ANGKUT DI PT. BAGUS JAYA ABADI KOTA SORONG PROVINSI PAPUA BARAT DAYA - lamria, Renta; Hutapea, Ricardo O.M. (INTAN Jurnal Penelitian Tambang, 2024)
Bagus Jaya Abadi is a mining company located in Sorong City, Southwest Papua Province that uses quarry mining to extract andesite rock. The effectiveness of production equipment, such as excavators and dump trucks, is essential to meet production targets. However, operational challenges and weather conditions often hinder the achievement of these targets. This study aims to calculate the daily production rates of Caterpillar 320D and Komatsu PC 200 excavators when loading Hino 300 and Hino 260 dump trucks and evaluate the work efficiency of these machines. Results indicate that daily production rates for different equipment combinations vary between 145.36 m³/day and 221.93 m³/day, depending on the pairing of machinery. These findings provide a foundation for the company to improve production efficiency and develop strategies to address existing challenges.